2017
DOI: 10.1080/17797179.2017.1306827
|View full text |Cite
|
Sign up to set email alerts
|

Fluid-solid-electric energy transport along piezoelectric flags

Abstract: The fluid-solid-electric dynamics of a flexible plate covered by interconnected piezoelectric patches in an axial steady flow are investigated using numerical simulations based on a reduced-order model of the fluid loading for slender structures. Beyond a critical flow velocity, the fluid-solid instability results in large amplitude flapping of the structure. Short piezoelectric patches positioned continuously along the plate convert its local deformation into electrical currents that are used within a single … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 38 publications
(71 reference statements)
0
3
0
Order By: Relevance
“…The introduced mechanical set-up shows for the first time after the 80-years-old Reut's paper, that a load acting on a fixed line can be made a real and usable condition, thus opening the way to new and unexpected applications, for instance in mechanical actuation or energy harvesting [18], but also in models for locomotion [19], biomechanics [20], and fluid-structure interaction [21], research arenas where flutter instability may play an important role. 2 Elastic double pendulum subject to four different loads of conservative and nonconservative nature A double pendulum is considered, namely, the two-degree-of-freedom rigid and heavy (the rods have unit mass densities ρ 1 , ρ 2 , and ρ 3 ) rods system shown in Fig.…”
Section: Introductionmentioning
confidence: 99%
“…The introduced mechanical set-up shows for the first time after the 80-years-old Reut's paper, that a load acting on a fixed line can be made a real and usable condition, thus opening the way to new and unexpected applications, for instance in mechanical actuation or energy harvesting [18], but also in models for locomotion [19], biomechanics [20], and fluid-structure interaction [21], research arenas where flutter instability may play an important role. 2 Elastic double pendulum subject to four different loads of conservative and nonconservative nature A double pendulum is considered, namely, the two-degree-of-freedom rigid and heavy (the rods have unit mass densities ρ 1 , ρ 2 , and ρ 3 ) rods system shown in Fig.…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, at wind velocity of 10 m s −1 , the maximum power reaches ≈290 μW. Xia et al [ 43 ] numerically described the large amplitude flapping dynamics of a PZT flag immersed in a free‐stream flow, comprising a flexible plate covered by interconnected PZT patches. Their investigations revealed that maximum energy production from their harvester can be achieved when the output resistance is located in close proximity to the end of the flag.…”
Section: Introductionmentioning
confidence: 99%
“…Fluid-solid-electric coupling in a piezoelectric flag have thus been considered and result in the lock-in of the flapping motion onto the natural frequency of the output electric circuit, which significantly affects their energy harvesting efficiency [33]. Furthermore, continuous circuit models of piezoelectric flags showed some further coupling and organization of the energy transport along the solid and electric systems [34]. The coupling of a flag to a mechanical resonant system through the rotation of its mast also displayed the possibility of lock-in and increased energy transfer [35].…”
Section: Introductionmentioning
confidence: 99%